Causal Loop Diagram for Better Understanding of Customer Satisfaction in The Indonesian Public Service - Rahajeng Puput Aryani; Manahan Siallagan (AIBPM Publisher, 2021)
In Indonesia, public service providers were mandated to measure consumer satisfaction in improving the quality of their services. It could help the organization to establish the priority of areas that need to be improved. On the other hand, the customer satisfaction index is frequently analyzed using a linear thinking technique, in which an event is continuously seen from a particular point of view, perhaps leading to policies that are contrary to what the customer expects. This research aimed to adopt a more systematic approach for better understanding the structures that generated customer satisfaction, so the various policies could be designed to address the problems that arise. A causal loop diagram (CLD) was used to describe the feedback structure of interrelationships among variables, allowing for identifying the structure that generated customer satisfaction. The structure showed how customer satisfaction was formed and how it affected other variables. The conceptual CLD is a mental map constructed to highlight various cause-and-effect interactions and to disclose some relationships between customer satisfaction variables that are important in policymaking related to customer satisfaction.